Cali, “World capital” of drug trafficking: an urban image from abroad - Mayor, Camilo Adolfo (Sociedad y Economía, 2010)
Cali, sports capital, civic city and seat of drug trafficking, three urban social representations, is the title the research made to complete the master studies in sociology. In these three social representations, the reader will find the results about the last urban images addressed in the review of the local newspaper El País. The most significant fact is the death of the head of the so-called poster of Medellin, Pablo Escobar, at the end of 1993. Here it’s described how did that image was created, who impulse it, why, and what was the relationship with the social reality of the city then. In the end, some conclusions are given, and these give an account at the inner dynamic of the formation and operation of a social representation in context.